Value-Based Intermediation in the International Expansion Strategy of Halal Food Companies Post-Trade Liberalization - Ahmad Syaichoni; Amalia Nuril Hidayati; Rama Wahyu Sampurno; Sisilia Anggraini (Talaa : Journal of Islamic Finance, 2025)
Trade liberalization has reshaped the competitive landscape of Indonesia’s processed food industry, including halal food companies that must navigate market expansion while maintaining Shariah compliance. This study analyzes how halal food firms integrate the Value-Based Intermediation (VBI) framework into their international expansion strategies following tariff reductions and the removal of non-tariff barriers. Utilizing a mixed-method approach—combining quantitative analysis of trade and investment data (BPS and UN Comtrade) with qualitative case studies of Indofood and Mayora—the research reveals that firms are not solely pursuing economic efficiency, but also embedding Islamic ethical values such as social sustainability, local farmer empowerment, and halal assurance into their strategies. Key initiatives include the establishment of halal compliance units, alignment with Shariah-compliant financing, and the implementation of risk governance frameworks inspired by maqashid al-shariah. The findings confirm that VBI can serve as an effective strategic model to guide halal food companies in balancing global trade opportunities with their religious and ethical obligations, thereby enhancing both competitiveness and sustainability.